Strategi Persuasi dalam Judul Video Dakwah Islam di YouTube Indonesia melalui Sinergi Tindak Tutur dan Perangkat Stilistika - Sukardi, Mochamad Ighfir; Susetya, Hemas Haryas Harja; Santoso, Anang; Martutik, Martutik (Hasta Wiyata, 2026)
This study investigates speech act patterns and pragmastylistic strategies employed in Islamic video titles on Indonesian YouTube and explains how both dimensions interact to construct persuasive digital religious communication. Using a qualitative descriptive approach, the study analyzed 150 Islamic video titles selected purposively from Indonesian YouTube channels. Data were examined through qualitative content analysis by classifying speech acts, stylistic devices, and communicative functions based on speech act theory and pragmastylistics. The findings indicate that representative, directive, and expressive speech acts are the most dominant categories, accompanied by collaborative speech act patterns that combine multiple illocutionary forces within a single title. Stylistically, irony, hyperbole, antithesis, repetition, and various forms of linguistic foregrounding are frequently employed to strengthen communicative effects. The analysis further demonstrates that persuasive power is generated not by speech acts or stylistic devices independently but through their systematic interaction, producing stronger pragmatic effects within the attention economy of digital platforms. This study extends the application of pragmastylistics to digital religious communication by demonstrating that YouTube video titles function as strategic sites where religious messages, audience engagement, and platform-specific communication practices are negotiated.